Systemic inflammatory response syndrome is more associated with bacteremia in elderly patients with suspected sepsis in emergency departments. Issue 49 (December 2016) - Chou, Hsien-Ling; Han, Shih-Tsung; Yeh, Chun-Fu; Tzeng, I-Shaing; Hsieh, Tsung-Han; Wu, Chin-Chieh; Kuan, Jen-Tse; Chen, Kuan-Fu
Abstract : Abstract: Early diagnosis of bacteremia for patients with suspected sepsis is 1 way to improve prognosis of sepsis. Systemic inflammatory response syndrome (SIRS) has long been utilized as a screening tool to detect bacteremia by front-line healthcare providers. The value of SIRS to predict bacteremia in elderly patients (≥65 years) with suspected sepsis has not yet been examined in emergency departments (EDs). We aimed to evaluate the performance of SIRS components in predicting bacteremia among elderly patients in EDs. We retrospectively evaluated patients with suspected sepsis and 2 sets of blood culture collected within 4 hours after admitting to ED in a tertiary teaching hospital between 2010 and 2012. Patients were categorized into 3-year age groups: young (18–64 years), young-old (65–74 years), and old patients (≥75 years). Vital signs and Glasgow Coma Scale with verbal response obtained at the triage, comorbidities, sites of infection, blood cultures, and laboratory results were retrieved via the electronic medical records. A total of 20, 192 patients were included in our study. Among them, 9862 (48.9%) were the elderly patients (young-old and old patients), 2656 (13.2%) developed bacteremia. Among patients with bacteremia, we found the elderly patients had higher SIRS performance (adjusted odds ratio [aOR]: 2.40, 95% confidence interval [CI]: 1.90–3.03 in the young-old and aOR: 2.66, 95% CI: 2.19–3.23 in the old). Fever at the triage was most predictive of bacteremia, especially in the elderly patients (aOR: 2.19, 95% CI: 1.81–2.65 in the young-old and aOR: 2.27, 95% CI: 1.95–2.63 in the old), and tachypnea was not predictive of bacteremia among the elderly patients (all P > 0.2). The performance of SIRS to predict bacteremia was more suitable for elderly patients in EDs observed in this study. The elderly patients presented with more fever and less tachypnea when they had bacteremia.